Emotional Wellbeing: The Impact of the COVID-19 Pandemic on Women Academics in South Africa - Ronnie, Linda; Bam, Armand; Walters, Cyrill (Frontiers in Education, 2022)
After the World Health Organization declared COVID-19 a pandemic on 11 March 2020, countries around the world responded with state-mandated lockdowns. Emerging data on the adverse psychological impact of the lockdown shows that women as a whole are among the most vulnerable groups. This study explores the specific stressors manifesting for women academics during lockdown and their toll on emotional wellbeing. A qualitative interpretive analysis of responses from 2,029 women academics showed participants were experiencing stress, fatigue, and burnout as the result of emotional taxation from three sources: home responsibilities, social milieu, and work environment. The work-life merge that occurred during lockdown seemed to have a concertina effect on emotional wellbeing as participants were pressured to manage an inordinate number of responsibilities at once. The specific consequences of the concertina effect found in this study highlight opportunities for the academy to better support the wellbeing of women academics.